PENGARUH LABEL HALAL TERHADAP KEPUTUSAN MASYARAKAT MEMBELI PRODUK MAKANAN DAN MINUMAN (Studi Kasus Lingkungan VI Kelurahan Nangka Binjai Utara) - Raja Sakti Putra Harahap (Universitas Islam Negeri Sumatera Utara, 2020)
This study aims to determine how the effect of the halal label on people’s decisions to buy food and beverage products. The method used is a quantitative method with a simple regression model and using statistical tests with the help of IBM SPSS Statistics 22 for windows. The sample in this study is the neighborhood community VI Nangka Village as many as 70 respondents. The results showed that the calculated r value was 0,79, so it could be saidthat there was s relationship or correlation between the variables X (Halal Label) with the variable Y ( The decision to buy food and beverage products). Then the t value < t table, which has a value of 0,657 < 1,668. Then is accepted and is rejected, which means that partially (X) variable does not have a significant effect on variable (Y), where the results of the hypothesis are accepted and proven after being calculated using a simple regression formula, namely Y = 34,7 + 0,67X. By having a regression coefficoent of 0,675%, so the halal label has a positive effect on decisions to buy food and beverage products.